PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN - Etik Prihatin; Syadza Zahirah Jamaluddin; Muh Haerdiansyah Syahnur (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This study aims to determine and examine the effect of service quality which includes physical evidence, empathy, reliability, responsiveness, and assurance on patient satisfaction at Wonokerto Sukamaju Health Center. This study involved 103 patients at Wonokerto Sukamaju Health Center who were selected using a purposeful sampling technique. This study used primary data collected through questionnaire surveys and secondary data collected from the literature. The findings show that physical evidence, reliability, responsiveness, certainty, and empathy together have a positive and significant effect on patient satisfaction. Partially, Physical Evidence has a positive and significant effect, while Reliability and Responsiveness have a positive but insignificant effect. Finally, the variables of certainty and empathy have a negative and insignificant effect on patient satisfaction